Strategi Ketahanan Keluarga Dengan Konsep Stifin Personality Perspektif Maqashid Al-Syari’ah - Subhan, Muhammad; Arisman, Arisman; Nelli, Jumni (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
This research examines the family resilience crisis which originates from weak personality resilience factors resulting in very worrying decline.The presence of the STIFIn personality concept that collaborates sacred messages, psychology, neuroscience, fingerprint biometrics and uses advances in digitalisation technology is an alternative as a means of entry to identify the individual personalities of family members consisting of husbands, wives and children as a primary source of information that is very important to be used as the basis for strategic solutions to improve self-personality transformation to create family resilience. So that the purpose of family in line with the will of shari'ah (maqashid ash-syari'ah) which includes hifzu al-din, hifzu al-nafs, hifzu al-'aql, hifzu al-nasb and hifzu al-mal can be realised. This research wants to reveal the correlation of the STIFIn Personality concept that is simple, accurate and applicable and scientific to determine the transformation of one's personality in family members and face efforts to increase family resilience. To realise this goal, this research uses qualitative research methods with a library research approach and explores information, data and supporting facts from relevant primary and secondary sources. Furthermore, it is analysed descriptively. The results show that the concept of STIFIn personality is very effective and relevant to determine a person's personality and deserves to be used as a strategic method for solving the family resilience crisis that starts from personality factors in accordance with the maqashid ash-shariah frame.